PENGARUH PENGGUNAAN KALIUM HIDROKSIDA DAN ASAM FOSFAT TERHADAP AKTIVITAS AMPAS KOPI DALAM PENGOLAHAN MINYAK JELANTAH - Rika Endara Safitri (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2026)
Coffee grounds contain various components, namely total carbon with a content of 47.8-58.9%, total nitrogen 1.9-2.3%, ash 0.43-1.6%, and cellulose as much as 8.6%. The high carbon content in coffee grounds makes it suitable for use in the manufacture of activated carbon. In this study, the utilization of coffee grounds is increased as an adsorbent by processing it into activated carbon material. Chemical carbon activation can use acidic, basic, or salt chemicals such as hydrogen chloride (HCl), phosphoric acid (H3PO4), potassium hydroxide (KOH), potassium carbonate (K2CO3), and zinc chloride (ZnCl2). In this study, KOH and H3PO4 were used as activated carbon activator compounds in coffee grounds. To determine the level of ability of potassium hydroxide and phosphoric acid as coffee grounds activators, used cooking oil was used as one of the application media. In this study, it can be concluded that the use of phosphoric acid in the coffee grounds activation process can increase the absorption capacity compared to the use of potassium hydroxide.